The readability of medicine label amongst senior citizen / Irwan Zakaria - Zakaria, Irwan (2012)
Preliminary study have proved that elderly person have a problem in reading their prescription medication labels. Questionnaire surveys were conducted in five local clinics involving 200 respondents. Targeted respondents were individual with low vision; whose are unable to read printed materials at a normal viewing distance, without reading glasses or contact lenses. Respondent's average age were between 45 - 65 years old. Results from questionnaire conducted revealed that most respondents have difficulties in reading existing medication labels. Thus, new prescription medication label was proposed. The new proposed prescription medicine label employs larger print fonts (14 point), incorporates cautionary and expiry date. Generic medicine name was also included and the uses of the medicine were printed underneath. Most consumers prefer the new prescription medicine label with larger font size when compared to the current prescription medicine label. The evaluation of the new label has shown that prescription medicine label with larger font size can be introduced into local clinics with a minimum disruption to workflow.